87PNegative to positive lymph node ratio-prognostic marker of survival in node positive rectal cancer. (24th November 2019) - Jonnada, P K; R, R A; C, R; Syed, A; C, S
Abstract: Background: Survival outcome in rectal cancer primarily determined by nodal status and stage of tumour. Though nodal invasion is strong prognostic indicator in rectal cancer, there exists marked heterogenecity within stage III patients. We investigated the prognostic impact of ratio of positive lymph nodes to total number of retrieved nodes (LNR), ratio of positive to negative lymph nodes (PN-LNR) and negative to positive nodes (NP-LNR) on survival in patients with node positive rectal cancers. Methods: This is a retrospective analysis of 336 patients of rectal cancer who underwent surgery and adjuvant therapy between 2011 to 2014. The node positive patients were grouped into two groups based on quartiles of LNR <0.2 and >0.2, PN-LNR <0.36 and >0.36 and NP-LNR <2.38 and >2.38. The association between LNR, PN-LNR and NP-LNR and survival was evaluated by the Kaplan-Meier method and multivariate analysis with covariates of prognostic significance in univariate analysis. Results: Patients classified as LNR <0.2 and >0.2 had a 5-year OS of 86.8 and 64.4 (p < 0.001) and DFS of 85.4 and 59.9 respectively (p < 0.001). The 5-year OS rate for PN-LNR <0.36 and >0.36 were 85.1 and 55.1 (p < 0.001) and DFS of 83.9 and 49.3 respectively (p < 0.001). The 5-year OS rate for NP-LNR <2.38 and >2.38 were 53.1 and 87.3 (p < 0.001) and DFS of 47.5 and 85.6 respectively (p < 0.001). OS and DFS of stage III A, III B, III C were 80.3, 75.3, and 53.3 (p < 0.001) and 79.5, 71.8 and 47.8 respectively (p < 0.001). On univariate analysis, pN status, sex, grade, histology of tumour, LNR, PN-LNR, NP-LNR were found to be significator factors for OS. On multivariate analysis, NP-LNR was found to be significant factor for OS. (p < 0.001, HR = 17.857; [3.557-89.657]). Factors that were found to be significant for DFS were pN status, LNR, PN-LNR, NP-LNR on univariate analysis and NP-LNR on multivariate analysis. (p < 0.001, HR = 11.41; [1.928-67.634]). NP-LNR is found to a significant factor for OS and DFS both on univariate and multivariate analysis. Conclusions: The NP-LNR was recognised as an independent prognostic factor in node positive rectal cancer patients. Hence, it can be used as an independent prognostic factor and permits superior prognostic stratification in stage III rectal cancer. Legal entity responsible for the study: Kidwai Memorial Institute of Oncology. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.